CHARACTERISTICS AND DEVELOPMENT OF CREATIVE TOURISM IN BANDUNG - Firmansyah, Ricky; Rosyidie, Arief (ASEAN Journal on Hospitality and Tourism, 2017)
Nowadays, creative tourism has been developing in Bandung, proved by the existence of eight creative tourism attractions. The characteristics of those creative tourism attractions were dominated by art-based creative tourism which was created by the development of creative industries and many requests from the tourist on how to make creative products. The main problems on the development, both internal and external creative tourism attractions, was lack of qualified local human resources. The creative tourism development in Bandung was also influenced by internal and external factors, either encouraging or inhibiting the development.